LITERACY EFFORTS IN INCREASING READING INTEREST IN CLASS 3 SDN CILELES - Ujang Jamaludin; Sigit Setiawan; Adlin Putri Pinanggih; Chelsi Arnita; Nandia Miftahul Aphdal (Institut Pendidikan Indonesia, 2023)
The purpose of this research is to find out the role of literacy activities, barriers and efforts made by the school to increase students interest in reading priimary school. This research is a qualitative research. Research subject are teacher and grade III student at SD Negeri Cieles. Data collection tecniques through interviews, observation and docuenation. Based on the results of the research, it can be seen that 1) literacy activities play a role in increasing students interest in readin, 2) obstacles in implementing literacy activities in schools include the lack of infrastructure, the methods applied are less varied and the students discipline is low in the process of grtting used to literacy activities, and 3) the efforts made by parties school in overcoming these obstacles is to provide socialization reganing literacy activties, adding facilities and organizing competition activities as a mean of active participation of student.